MANAGEMENT OF THE ISSUE OF DELAYS IN THE DISBURSEMENT OF ELECTION PANTARLIH HONORS FOR THE 2024 ELECTION IN EAST JAVA VIA INSTAGRAM - Ayu, Alrisa (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2023)
This study is a discourse regarding the issue management of the East Java Provincial KPU to overcome issues developing on social media, in this article the East Java Provincial KPU's Instagram due to delays in disbursing the honorarium for the Officer for Updating the Voter List (Pantarlih) for the 2024 Election in East Java. The practice of issue management cannot be separated from the role of Public Relations which manages the East Java Province KPU Instagram. Then, the aim of the study is to find out the East Java Province KPU's issue management efforts and understand its policy direction. The research uses a qualitative approach, with data collection methods namely observation, interviews, and document study. The selection of informants is determined based on certain criteria. The results of the study show that the East Java Province KPU has made several efforts to overcome this problem. The issue management carried out made the East Java Province KPU provide direction to internal parties and provide clarification in public. This clarification is one way to solve problems that occur between the public and agencies. Meanwhile, the East Java Provincial KPU took firm action against the parties responsible for Honor Pantarlih.